Detection of DNA Hybridization Using Protein A Modified Ion Sensitive Field Effect Transistor - Nang Mo Hom (2018)
© 2015, Copyright © Taylor & Francis Group, LLC. A DNA sensor based on an ion sensitive field effect transistor (ISFET) with protein A modification for characterization of DNA hybridization is reported. The surface of the ISFET was modified with protein A via physical adsorption. Protein A binds specifically to the crystallizable fragment of the antibody leading to uniform orientation of the antigen binding site. In order to characterize DNA hybridization, the antibiotin antibody was immobilized to protein A and a single-strand biotinylated DNA probe was added to bind to a specific antibiotin antibody. The voltage shift of the DNA hybridization was observed after the complementary DNA target was added to the immobilized probe. The noncomplementary DNA target was also tested as a negative control. The optimal concentrations were 1 mg/mL for protein A, 1 mg/mL for the anti-biotin antibody, 0.5 µM for the biotinylated probe, and 0.5 µM for the synthetic DNA target. Nevertheless, high concentrations of protein A and antibiotin may prevent the hybridization signal detection; therefore, 0.1 mg/mL of protein A and antibiotin were employed instead of their optimal concentrations. By this strategy, DNA hybridization of the synthetic target was successfully measured with a limit of detection of approximately 0.08 µM. In addition, complementary DNA was differentiated from a noncomplementary DNA target.